Including diverse knowledges and worldviews in environmental assessment and planning: the Brazilian Amazon Kaxinawá Nova Olinda Indigenous Land case. Issue 1 (1st January 2020) - Matuk, Fernanda Ayaviri; Behagel, Jelle Hendrik; Simas, Felipe Nogueira Bello; Do Amaral, Eufran Ferreira; Haverroth, Moacir; Turnhout, Esther
ABSTRACT: The concepts of 'ecosystem services' (ES) and 'nature's contributions to people' (NCP) inform environmental frameworks that set out to include Indigenous and Local Knowledge systems (ILK) and worldviews in policy and planning processes. These frameworks aim to enhance biodiversity conservation and human well-being in a legitimate and effective way. In this article, we explore how the concept of People's Contributions to Nature (PCN) is complementary to NCP. We use it to investigate challenges that planners and locals face in realizing the legitimate inclusion of diverse knowledges and worldviwes that account for people and ecosystems in a relational way. We introduce a case study where planners drew on ES and NCP and used participatory methods to implement a REDD+ policy in the Kaxinawá Nova Olinda Indigenous Land (Acre-Brazil). We find that both Kaxinawás and planners emphasize both NCP and PCN in their discourses. Nevertheless, differences between knowledge systems and disciplines, uneven power relations between Kaxinawás and planners, and an under-consideration of PCN by global frameworks challenge the legitimate inclusion of the Kaxinawá knowlege and worldviews to craft assessment and planning. We conclude that by explicitly addressing these challenges, science-policy interfaces can further advance knowledge legitimacy and policy effectiveness.EDITED BY Harini Nagendra